Cloning of the RHO1 gene from Candida albicans and its regulation of beta-1,3-glucan synthesis. - Kondoh, O (1997)
The Saccharomyces cerevisiae RHO1 gene encodes a low-molecular-weight GTPase. One of its recently identified functions is the regulation of beta-1,3-glucan synthase, which synthesizes the main component of the fungal cell wall (J. Drgonova et al., Science 272:277-279, 1996; T. Mazur and W. Baginsky, J. Biol. Chem. 271:14604-14609, 1996; and H. Qadota et al., Science 272:279-281, 1996). From the opportunistic pathogenic fungus Candida albicans, we cloned the RHO1 gene by the PCR and cross-hybridization methods. Sequence analysis revealed that the Candida RHO1 gene has a 597-nucleotide region which encodes a putative 22.0-kDa peptide. The deduced amino acid sequence predicts that Candida albicans Rho1p is 82.9% identical to Saccharomyces Rho1p and contains all the domains conserved among Rho-type GTPases from other organisms. The Candida albicans RHO1 gene could rescue a S. cerevisiae strain containing a rho1 deletion. Furthermore, recombinant Candida albicans Rho1p could reactivate the beta-1,3-glucan synthesis activities of both C. albicans and S. cerevisiae membranes in which endogenous Rho1p had been depleted by Tergitol NP-40-NaCl treatment. Candida albicans Rho1p was copurified with the beta-1,3-glucan synthase putative catalytic subunit, Candida albicans Gsc1p, by product entrapment. Candida albicans Rho1p was shown to interact directly with Candida albicans Gsc1p in a ligand overlay assay and a cross-linking study. These results indicate that Candida albicans Rho1p acts in the same manner as Saccharomyces cerevisiae Rho1p to regulate beta-1,3-glucan synthesis.